2021
DOI: 10.4251/wjgo.v13.i10.1317
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder cancer: Historical treatment and new management options

Abstract: Gallbladder cancer is a rare, aggressive malignancy that has a poor overall prognosis. Effective treatment consists of early detection and surgical treatment. With the wide spread treatment of gallbladder disease with minimally invasive techniques, the rate of incidental gallbladder cancer has seen an equitable rise along with stage migration towards earlier disease. Although the treatment remains mostly surgical, newer modalities such as regional therapy as well as directed therapy based on molecular medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 107 publications
0
17
0
1
Order By: Relevance
“…Small cell gallbladder carcinoma has a poor prognosis, with 5-and 10-year rates of relative survival of 8% and 0%, respectively [12]. Several staging methods for gallbladder cancer have been reported, including Nevin's staging system (Table 3), the Japanese Biliary Surgical Society staging system (Table 4), and the American Joint Committee on Cancer TNM staging system (Table 5) [13][14][15].…”
Section: Non-neoplastic and Neoplastic Lesions Of The Gallbladdermentioning
confidence: 99%
“…Small cell gallbladder carcinoma has a poor prognosis, with 5-and 10-year rates of relative survival of 8% and 0%, respectively [12]. Several staging methods for gallbladder cancer have been reported, including Nevin's staging system (Table 3), the Japanese Biliary Surgical Society staging system (Table 4), and the American Joint Committee on Cancer TNM staging system (Table 5) [13][14][15].…”
Section: Non-neoplastic and Neoplastic Lesions Of The Gallbladdermentioning
confidence: 99%
“…Gallbladder cancer is a rare malignancy with poor prognosis owing to its late diagnosis and rapid progression [ 266 ]. PKCι is upregulated and correlates with poor prognosis in patients with gallbladder cancer.…”
Section: Pkc Isozymes As Prognostic Biomarkers or Therapeutic Targets...mentioning
confidence: 99%
“…Gallbladder cancer (GBC) is the most common malignancy of the biliary tract and is usually diagnosed late in the course of the disease, with a poor overall prognosis ( Baiu and Visser, 2018 ). Clinical treatment is still predominantly surgical, but newer therapeutic modalities, such as molecular targeted therapy, have been used to improve the prognosis of patients with advanced disease ( Kam et al, 2021 ; Okumura et al, 2021 ). Recent studies have shown that a variety of exosomal miRNAs, lncRNAs, miRNAs, and circRNAs can be used as clinical diagnostic biomarkers for GBC ( Xue et al, 2020 ; Ren et al, 2021 ; Ueta et al, 2021 ).…”
Section: Roles Of Msc-derived Exosomes In Gi Cancersmentioning
confidence: 99%